STRATEGI PEMASARAN DALAM MENINGKATKAN KOMERSIALISASI HASIL LITBANG (KASUS: BALIT PALMA) - Surminah, Iin (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
The objectives of this study are first, to give a broad picture of marketing pattern of R&D output and second, to describe the marketing strategy of R&D output done by Balitka. The important considerations in improving marketing are: (1) technology capabilities; (2) human resource competencies; (3) research budget capabilities (4) capabilities of infrastructures, laboratories, and other working equipment; (5) capabilities of after sales services; and (6). quality standard; Those six aspects are the main resources to produce qualified R&D output that is able to be implemented by the users. Besides those Balit Palma considers the government policy related to R&D institutions which have applied their R&D output to the users.